CREEP BEHAVIOR AND CONSTITUTIVE DESCRIPTION OF POLYTETRAFLUOROETHYLENE UNDER TEMPERATURE-STRESS COUPLING - WANG JingHui; LI JiKang; LIU Zheng; CHEN Xu (Jixie qiangdu)
Polytetrafluoroethylene(PTFE)has the advantages of high and low temperature resistance,chemical corrosion resistance and high thermal stability,and has become an indispensable sealing material in the industrial field.Its compression performance is crucial to the safe service of the sealing structure.By carrying out the compression experiments and compression creep experiments on PTFE,the compression properties of PTFE at different temperatures were studied,and the coupling effect of stress and temperature on creep behavior was explored.The results show that the compressive yield strength and compressive modulus of PTFE decrease with the increase of temperature.The compression creep performance is influenced by the coupling of temperature and stress.At the same temperature,the instantaneous strain and creep rate of PTFE increase with the increase of stress.Under the same stress,as the temperature increases,the compressive modulus decreases,the molecular energy and free volume increase,resulting in an increase in the instantaneous strain and creep of PTFE,and an increase in the total strain.Finally,the Burgers model,Findley model,and Time-Hardening model were used to analyze the creep behavior of PTFE under different loading conditions.It was found that the Burgers model and Findley model can better describe the creep behavior of PTFE at different temperatures.This study can provide theoretical guidance and data support for the design and engineering application of sealing structures that consider the compressive creep performance of PTFE.